Antifungal Activity against Aspergillus parasiticus of Supernatants from Whey Permeates Fermented with Kefir Grains - Gamba, Raúl (2015)
Aspergillus parasiticus, a common fungal contaminant in food, produces aflatoxin B1, which is classified as human carcinogen. Kefir is an ancient fermented beverage obtained by the fermentation of different substrates with kefir grains. A very important waste produced by the dairy cheese industry is the whey permeate, which nowadays is a strong ambient contaminant. The aim of this work was to assess the effect of whey permeates fermented with kefir grains against A. parasiticus growth, aflatoxin B1 biosynthesis, and the kefir microorganisms protection against the cell damage produced by aflatoxin B1. It was observed that kefir-cell-free-supernatants (CFS) produced fungal inhibition. A fungicidal effect was observed with 65% v/v of CFS in the culture medium (final pH 4.55 and total undissociated lactic and acetic acid concentration 34.08 mM). Under these conditions, aflatoxin production was not detected. Finally, it was found that non-viable kefir microorganisms protected HepG2 cells from the damage produced by aflatoxin B1.